Accelerated capacity model of lithium-ion battery based on non-linear polynomial method with stress coupling analysis under two electrical variables. (15th June 2022) - Hou, Yandong; Peng, Yu; Liu, Datong
Highlights: A novel acceleration model under two electrical variables for lithium-ion battery is proposed. The proposed method is developed with stress coupling based on the non-linear polynomial model. The proposed method is evaluated using lithium-ion batteries with accelerated degradation test under two electrical variables. Abstract: For lithium-ion batteries, accelerated degradation test (ADT) plays a pivotal role for their long cycle life and high reliability. In some applications, the degradation of batteries is affected by the electrical stresses. Hence, the extended Eyring model applied with the temperature coupling other non-thermal stress, is not appropriate. Motivated by this idea, a non-linear polynomial method with stress coupling analysis (NLP-SCA) model for double electrical variables is proposed as it can extend the application scenarios of current acceleration model. Meanwhile, the NLP-SCA is also developed with better goodness-of-fit compared with the models, by which the stress couplings are ignored. For the life estimation with normal condition, four evaluation criterions (root mean square error, R-Squared, sum of squares due to error, and the mean absolute error) calculated with the proposed model increase by 45.37%, 42.15%, 3.94% and 8.17% separately, compared to the general polynomial acceleration model and exponential acceleration model.